The Development of CIHOE Game As A Learning Media In The Elemental Chemistry Material - Fatimah, Nuril; Hidayah, Rusly (International Journal of Active Learning, 2021)
The purpose of the research are to develop CIHOE "Chemistry Island: Heaven Of ElementsÃ¢â‚¬Â game as a learning media in elemental chemistry material and also to test the validity, practicality and the effectiveness of the game. The method that used in this research is Gall and Borg development model. The steps are limited to the preliminary field testing. The preliminary field testing step was conducted using one group pretest posttest design. The instrument that used are validation questionnaire, observation sheet, studentÃ¢â‚¬â„¢s response questionnaire, pretest and posttest questions. Data collection were conducted with 15 students of SMAN 1 Menganti. The validity of the game is 91,25 %, which means very valid. The practicality value of the game is 92,6 % which means very easy to operate and useful. The observation result of the studentÃ¢â‚¬â„¢s learning activity is 98,57 %. The classical completeness at the pretest is 13 %, while in the posttest reaches 93 %. It means that CIHOE game is very effective to be used as a learning media in elemental chemistry material. By the development of CIHOE game, researcher hopes that it will help chemistry teachers to explain elemental chemistry material.